OPTIMIZATION OF THE TWO POINT PROBE METHOD FOR THE CHARACTERIZATION OF PHOTOELECTRIC PROPERTIES OF MATERIALS - Boisandi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2024)
This research aims to obtain the electrical characteristics and photoelectric material measured by two point probe method using I-V measurement and to know the photoconductivity of the material measured by two point probe method with the multimeter circuit. Research using experimental method. The activities of research on the design of electrical characterization tools with two point probe method and optimization. Electrical characterization testing is carried out with material conductivity characteristics and compares it with a Elkahfi I-V meter as standar measurement. This result of research can be concluded that two point probe method with multimeter can be used to measure the conductivity and photoconductivity of the material. The results of conductivity measurement of ethanol as test solution using two point probe method is.